Arcabouço conceitual para computação reconfigurável - Molinos, Diego Nunes (2014)
The computing has over the years directing a radical change in the professional prole and personal of their users. In recent years can be seen, a growing increase of computing use as an auxiliary tool to solve problems. Problems that are increasingly common in dierent areas of knowledge. When the requirements of an application exceeds the capacity of the used solutions, new ways of solutions are developed to satisfy the demands of complexity. The reconfigurable computing has emerged as a computational solution model that integrate the xed hardware performance together with the software exibility, uniting the best of both paradigms. The reconfigurable computing is a eld relatively new and promising, where the main concepts and components that were present since its theoretical basis, still stands as the basis for the evolution of knowledge inside the area. Some of these concepts are older than other and those newer ones that arise due to the need for better understanding of the study eld. Currently has been noticed in the published articles that some concepts involving reconfigurable computing eld are being applied wrongly, on in other occasions, without exploit all their features. This lack of clarity in the use of concepts, aect the development of the study eld and contribute to the impoverishment of the area, aecting especially students and researchers in early stages of learning, that seeking through those articles a theoretical consistency. Indeed, a conceptual discussion within of any study eld, always has a significant importance for the any area. The conceptual framework proposed in this paper, aims to identify and present the conceptual denitions involving the recongurable computing eld, as well as their conceptual relationships. Within this framework we propose a organization model of concepts for recongurable computing, a concept map and all of the information is validated among a opinion consensus of several recongurable computing specialists. Moreover, this framework is intended to serve as a helper tool to the learning of recongurable computing, aiding in some methodological requirements as well as the increase of theoretical knowledge.